Fairness and satisfaction in buyer-supplier relationship - Perumal, Selvan; Mohd Noor, Nor Azila; Hussin, Zolkafli (2007)
The purpose of this conceptual paper to further understands the concept of fairness and satisfaction in buyer-supplier relationship perspective.The conceptual arguments put forward in this paper are based on review of satisfaction and fairness studies and research.As increase interest research in buyer-supplier relationship, satisfaction is viewed as an essential ingredient in the development and maintenance of long-term buyer-supplier relationships.This paper justifies the need for direct examination of fairness on satisfaction in buyer-supplier relationship.